Effect of tooth graft particle size on the healing process of femur defects in Wistar rat (Rattus norvegicus) - Malianawati Fauzia; Ega Lucida Chandra Kumala; Okky Satria Brilliando; Devi Amelia Ayu; Theresia Agata Winnitya Napitu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Teeth have potential as bone graft materials because of their organic and inorganic components that can stimulate osteoinduction, osteoconduction, and osteogenesis. An important success indicator of treatment using this graft material is the formation of osteoblast and new blood vessels in the applied area. Purpose: To investigate the number of osteoblast, osteoclast, and new blood vessels in bone healing after the implantation of tooth-derived bone graft materials measuring 20, 40, and 60 mesh. Methods: Thirty-six Wistar rats with a 2 mm defect on the right femoral dextra condile were divided into four groups. P0 (n=9) was the control group, where the defect was not filled by any material. In the other groups, the defects were filled by 20-mesh (P1; n=9), 40-mesh (P2; n=9), and 60-mesh (P3; n=9) tooth graft material. The Wistar rats were sacrificed after 2 weeks, and then the preparations were hematoxylin eosin staining. The data were analyzed using one-way analysis of variance and Tukey’s post hoc test. Results: The highest number of osteoblast was in the P3 group with a mean of 49.67, highest number of new blood vessels in the P2 group with a mean of 39.89, and highest number of osteoclast in the P1 group with a mean of 20.44. Statistical analysis showed a significant difference in the number of new blood vessels, osteoclast, and osteoblast in each group (p=0.000; p<0.05). Conclusion: Particle size differences in tooth graft material affect osteogenesis and angiogenesis in the bone healing process.